Approach to Healing Environment at A Heart Hospital in Surabaya - M H Syaifudin; W W Widjajanti; E Poedjioetami (Institut Teknologi Sepuluh Nopember, 2018)
Cardiovascular disease is the leading cause of death nearly 30% people around the world is caused by heart disease which comes from 80% poverty and developing countries. For Indonesia, cardiovascular disease also holds the record of non-communicable diseases with the highest case, especially East Java which is included the second predicate as the province with the largest heart disease. With the high mortality rate that occurs, it needs to plan a building that can be a service heart disease supporting the ideal healing process. Healing environment approach can pay attention to hospital building/hospital design which gives positive effect both physically and psychologically can make the healing process within the hospital itself. With the take this approach is considered in the heart hospital in Surabaya can make the hospital that can support the healing process optimally. The final result of heart hospital design in Surabaya with healing environment concept, the design of heart hospital to adjust to the environment around the site by putting forward three design approaches that are nature, senses, and psychological. With the heart hospital in Surabaya is expected to give benefits to the community in the face of heart disease is increasing from year to year.